2018
DOI: 10.1002/nop2.230
|View full text |Cite
|
Sign up to set email alerts
|

Nurse competence in the interface between primary and tertiary healthcare services

Abstract: Aims (a) To explore nurses’ self‐assessed competence and perceived need for more training in primary and tertiary healthcare services; and (b) to investigate the factors associated with these issues. Design Quantitative, cross‐sectional, descriptive. Methods The ProffNurseSAS, the Job Satisfaction Scale and socio‐demographics were used. A convenient sampling method was used to invite registered nurses from 23 primary ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…A recent study found that supervisors perceive that students should learn most practical skills in the educational institution, while they should get further training in these skills when in clinical placements [ 20 ]. This may have an impact on supervisors' approach to, or facilitation of, students' learning of practical skills.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that supervisors perceive that students should learn most practical skills in the educational institution, while they should get further training in these skills when in clinical placements [ 20 ]. This may have an impact on supervisors' approach to, or facilitation of, students' learning of practical skills.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that RNs and IDNs perceive that students should learn both basic and advanced technical skills in the university college, and then practice further in clinical practice [ 28 ]. Moreover, another study showed that RNs in primary healthcare receive training in specific technical procedures such as handling of ventilators, tracheostomia, palliation or dialysis [ 9 ]. This complexity has also been indentified in international studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increasing implementation of technology enabled care in healthcare services leads to a need for reorganization of healthcare personnel’s working methods and services [ 7 ]. In addition, digital competence among healthcare personnel is still a challenge [ 8 ], and nurses express a need for more knowledge related to digitalization in healthcare services [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported competencies to manage clinical core components were measured using the Professional Nurse Self-Assessment Scale (PROFFNurseSASII) [12,13]. The scale consists of 50 items in six focus areas to avoid questions superfluous to the study aim.…”
Section: Competencies and Need For Further Trainingmentioning
confidence: 99%